GAMBARAN KEJADIAN IKUTAN PASCA IMUNISASI (KIPI) PASCA VAKSINASI COVID-19 PADA MAHASISWA KEPERAWATAN - Utami, Jewi; Kurniawan, Didi; Rustam, Musfardi (Coping: Community of Publishing in Nursing, 2022)
The COVID-19 pandemic is set to become a disturbing Public Health Emergency of International Concern (PHEIC) that requires a new strategy as an effective intervention, namely vaccination. The use of vaccines can cause vaccination reactions called Adverse Events Following Immunization (AEFI). This study aims to determine and explain the picture of Adverse Events Following Immunization (AEFI) post-COVID-19 vaccination in nursing students. This study used a retrospective descriptive design using univariate analysis. The research sample amounted to 649 respondents, with sampling using a total sampling technique. The measuring instrument used is the AEFI questionnaire via google form. The characteristics of respondent majority of late adolescents aged 17-25 years of 639 (98,4%), with most of the female gender 578 (89,1%). The majority of Dose-1 vaccination types are Sinovac amounting to 581 (89,5%), Dose-2 vaccination the majority are also Sinovac at 338 (87,6%), and the majority Dose-3 vaccination is Pfizer-BioNTech totaling 113 (55,7%). Respondents experienced AEFI on Dose-1 vaccination with a total of 649 respondents, the most symptoms were muscle pain by 245 (37,8%), Dose-2 vaccination with a total of 386 respondents obtained the majority of muscle pain by 90 (23,3%), and vaccination Dose-3 with a total of 203 respondents, the majority of muscle pain was 65 (32,0%). The AEFI category in the Dose-1 vaccination was mostly in the low category by 290 (44,7%). The majority of Dose-2 vaccination AEFIs are in the low category of 225 (58,3%), and the majority of Dose-3 vaccinations are in the low category of 90 (44,3%). The most common AEFI symptom experienced by respondents is muscle pain, and the majority of AEFI post-COVID-19 vaccinations are in low category.